2019
DOI: 10.17582/journal.jahp/2019/7.2.51.57
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quinolones on Blood Glucose Level and Blood Profile of Laying Hens

Abstract: A study was designed to investigate the effects of quinolones antibiotics on the blood profile, blood glucose level, histomorphological features of pancreas and egg production of laying hens. For this purpose, a total of 48 laying hens were selected and allocated into four groups, each group included three replicates containing four birds in each. Three commonly used quinolones including enrofloxacin, ciprofloxacin and norfloxacin were used for four weeks with one week of adaptation period, while, one group se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
1
1
Order By: Relevance
“…Also, adding Tylosin at levels of 0.1, 0.2, or 0.3 g/kg to the diet of quail chicks led to a significant reduction in the concentrations of serum total protein and albumin, compared to the control group which had the highest values. This confirms the findings of [31], who found that the blood albumin levels of laying hens were not significantly affected (P>0.05) by the administration of quinolone antibiotics.…”
Section: Blood Constituentssupporting
confidence: 91%
See 1 more Smart Citation
“…Also, adding Tylosin at levels of 0.1, 0.2, or 0.3 g/kg to the diet of quail chicks led to a significant reduction in the concentrations of serum total protein and albumin, compared to the control group which had the highest values. This confirms the findings of [31], who found that the blood albumin levels of laying hens were not significantly affected (P>0.05) by the administration of quinolone antibiotics.…”
Section: Blood Constituentssupporting
confidence: 91%
“…The birds that were fed a diet with 0.3 g Tylosin /kg of the diet had the lowest levels of total cholesterol, while the birds given a diet with 0.1 g Tylosin /kg had the lowest levels of triglycerides, with the highest levels observed in the control group. This result not agree with [31] who noted that the impact of quinolones on cholesterol levels was observed to be statistically non-significant (P>0.05). However, [33] found that broiler chickens that received 15 g Polyalthia longifolia /L of the water had a significantly higher level of cholesterol compared to the control group.…”
Section: Blood Constituentscontrasting
confidence: 65%
“…This is a concern since the previous studies have reported the prevalence of multi-resistant Salmonella in animal food between 54.8% to 69.3% (Kamboh et al, 2018;Mikanatha et al, 2010). The high prevalence rates of MDR organisms in animal-origin food have been linked with antimicrobial agents such as tetracycline, penicillin and aminoglycoside which are been used frequently in animal husbandry (Ariffin et al, 2019;Rehman et al, 2019) and is therefore recognized as giant challenge in the veterinary and medical sciences to treat Salmonella infections (Thai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%